Archaeal lipid vaccine adjuvants for induction of cell-mediated immunity. (1st December 2016) - Haq, K.; Jia, Y.; Krishnan, L.
ABSTRACT: Introduction : Liposomal vesicles (archaeosomes) composed of total polar lipids (TPL) or semi-synthetic glycerolipids, unique to the domain Archaea, constitute potent vaccine adjuvant and delivery systems. The characteristics of this adjuvant offer a novel prospect for the development of effective vaccines for emerging infections and cancers, which is reviewed in this article. Areas covered : The areas covered in this review include the chemical composition and physical characteristics, various in-vitro and in-vivo pre-clinical immunogenicity and efficacy studies for systemic immunization, induction of mucosal immunity upon modification of the formulation with cations, and the mechanism of adjuvant action following uptake by antigen presenting cells. Expert commentary : The unique features of archaeal lipids confer archaeosomes with many desirable features. With the use of semi-synthetic archaeosomes, highly defined lipids that are safe and robust for induction of cell-mediated immunity may be chosen. These adjuvants function as Toll-like receptor-independent innate immune stimulants.